“Tutti gli occhi del mondo”: Court Networks between Turin and Madrid, 1640–1700 - Raviola, Blythe Alice (Renaissance and Reformation / Renaissance et Réforme, 2020)
Although the court of Turin’s role in the new balance of power in Europe during the War of the Spanish Succession is well known, far less is known about the strategic function of its collateral courts, such as the court of the princes of Savoy-Carignano. Based on the correspondence of the Savoy ambassador to Madrid, Costanzo Operti (1690–95), this article focuses on these courts to demonstrate the formal and informal diplomatic interplay among male and female aristocrats from 1640 to the end of the seventeenth century. One such noblewoman, Olimpia Mancini of Carignano-Soissons, was an Italian who grew up in the French court and maintained a close relationship with Louis XIV. As the wife of a prince of the Savoy-Carignano branch, she held important positions in Turin, Paris, and Madrid. Mother to the famous prince and military warrior Eugene of Savoy, after she lost her powerful status in France, she sought to find a place in the Madrid court as lady-in-waiting to Queen Marie Louise de Orléans. Her mother-in-law, Marie de Bourbon-Soissons, played an outstanding role in maintaining the honour and prestige of the court of Carignano.